IMPLEMENTASI KUALITAS PELAYANAN ASSURANCE KARYAWAN HOUSEKEEPING DEPARTMENT DI HARMONI SUITES HOTEL BATAM - Okta Bella Cen; Okki Kurnia (JURNAL MATA PARIWISATA, 2022)
The purpose of this study was to find out the implementation that occurs in service quality in the dimensions of assurance based on the theory of assurance component that consisting in communication, crediblity, security, competecy and courtesy, This type of research is descriptive qualitative research, research by analyzing, describing, and summarizing various conditions, situations from various data collected in the form of interviews or observations Based on the results of this study, we can see that housekeeping staff know about good and right skill communication for purpose the guest feeling comfortable and safe, but there is some miss communication between guest because of the language, know that privacy was important, always give the best service, and have a equal security system CCTV have a good maintenance in housekeeping area, have a qualified certification from PHRI, also have a good attitude with politeness, hospitable, also respect the elders Research suggestions for harmoni suites hotel, that expectly to be held a training or a program for learning foreign language especially Mandarin language for to decrease miscommunication that happen between guest and housekeeping staff